Defense genes expressed by chemical elicitors and Rhizoctonia solani infection in mungbean (Vigna radiata) - TRIPATHI, ARADHIKA; DUBEY, SUNIL C; TAK, RAKESH (The Indian Journal of Agricultural Sciences, 2023)
The effects of chemical elicitors salicylic acid (SA) and jasmonic acid (JA) on expression of defense genes PR 10, epoxide hydrolase (EH), catalase and calmodulin alone and with infection by Rhizoctonia solani were analysed using qPCR at 1–4 days post inoculation/application (dpi) in highly susceptible (HS; Ratna) and moderately resistant (MR; HUM1) varieties of mungbean [Vigna radiata (L.) Wilczek] during 2015 and 2016 at Indian Agricultural Research Institute, New Delhi and National Bureau of Plant Genetic Resources, New Delhi. In general, JA application in presence of R. solani upregulated the mean expression of these genes in both the varieties ranging from 1.8–11.9- fold, whereas SA application in presence of R. solani upregulated the mean expression from 1.2–3.4-fold. The JA and SA alone, also upregulated the expression of these genes in both HS and MR varieties with higher expression in MR variety. The expression of calmodulin and PR10 was higher at 1 dpi in HS variety while EH and catalase was higher at 4 dpi. In MR variety, PR10 was higher at 1 dpi and EH, catalase and calmodulin were over expressed at 4 dpi. The results clearly indicated that both JA and SA were responsible for upregulation of the defense genes in both HS and MR varieties of mungbean. The genes expression was accelerated in presence of R. solani at early stage of plant growth which delayed the infection caused by R. solani and helped to reduce disease development, hence may be used for the management of the disease.